Degradation of Spent Wash Colour: A Review of Treatment Methods (International Journal of Scientific Research in Science and Technology, 2025)
The global distillery industry plays a vital role in numerous economies but also produces large quantities of distillery spent wash (DSW), a highly polluting byproduct known for its high organic load, intense dark color, and low pH. In India alone, distilleries produce approximately 2.75 billion liters of alcohol annually, resulting in 30-45 billion liters of DSW. The dark color, primarily due to melanoidins, poses significant environmental challenges, including reduced light penetration in aquatic ecosystems and soil contamination. This paper provides a comprehensive review of DSW treatment technologies, focusing on color degradation. The review systematically categorizes treatment methods into physico-chemical, biological, and hybrid approaches, detailing their mechanisms, advantages, limitations, and cost-effectiveness. Physico-chemical methods like coagulation-flocculation, electrocoagulation, adsorption, and advanced oxidation processes (AOPs) show varying degrees of success in color and pollutant removal, though challenges like sludge generation and high energy consumption persist. Biological methods, including anaerobic digestion, aerobic treatment, and bioaugmentation, offer sustainable alternatives but are often limited by the recalcitrance of melanoidins. Hybrid methods, combining physico-chemical and biological treatments, demonstrate enhanced efficiency and potential for zero liquid discharge (ZLD). The paper also explores the utilization of treated DSW in agriculture, biogas production, and other valorization pathways, contributing to a circular economy. Despite progress, challenges remain in achieving complete color removal and cost-effective solutions. Future research should focus on developing innovative technologies, optimizing hybrid systems, exploring novel utilization strategies, and creating robust techno-economic models to promote sustainable DSW management practices. The ultimate goal is to transition from a linear waste management approach to a circular economy model, where DSW is viewed as a valuable resource rather than a waste product.